Impacts of Natural Organic Matter Adhesion on Irreversible Membrane Fouling during Surface Water Treatment Using Ultrafiltration - Fangshu Qu; Zhimeng Yang; Shanshan Gao; Huarong Yu; Junguo He; Hongwei Rong; Jiayu Tian (Membranes, 2020)
To understand impacts of organic adhesion on membrane fouling, ultrafiltration (UF) membrane fouling by dissolved natural organic matter (NOM) was investigated in the presence of background cations (Na+ and Ca2+) at typical concentrations in surface water. Moreover, NOM adhesion on the UF membrane was investigated using atomic force microscopy (AFM) with colloidal probes and a quartz crystal microbalance with dissipation monitoring (QCM-D). The results indicated that the adhesion forces at the NOM-membrane interface increased in the presence of background cations, particularly Ca2+, and that the amount of adhered NOM increased due to reduced electrostatic repulsion. However, the membrane permeability was almost not affected by background cations in the pore blocking-dominated phase but was aggravated to some extent in the cake filtration-governed phase. More importantly, the irreversible NOM fouling was not correlated with the amount of adhered NOM. The assumption for membrane autopsies is doubtful that retained or adsorbed organic materials are necessarily a primary cause of membrane fouling, particularly the irreversible fouling.